Увеличение чувствительности сенсоров изменения показателя преломления среды на основе поверхностного плазмонного резонанса - Ushenin, Yu. V.; Samoylov, А. V.; Khristosenko, R. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Results of computer modelling of an angular spectrum superficial plasmon resonance in metal films measurements with device PLAZMON-5 with infra-red radiator are analysed. It is shown that use of an infra-red source of radiation allows improving sensitivity of sensor device in comparison with source of visible light. On an example of dielectric refraction indexes measurement with PLAZMON-5 devise experimental check of theoretical calculations has been carried out.